Modulation of Blood Coagulation and Hematological Parameters by Crassocephalum crepidioides Leaf Methanol Extract and Fractions in STZ-Induced Diabetes in the Rat - Opeyemi O. Ayodele; Funmilayo D. Onajobi; Omolaja R. Osoniyi (The Scientific World Journal)
Diabetes affects the homeostasis of the circulatory system. Crassocephalum crepidioides Benth S. Moore (Asteraceae) is an edible plant locally used in the treatment of wounds, stomach ulcer, and skin-related conditions in Africa and some other parts of the world. This study investigated the effects of C. crepidioides leaf methanol extract and fractions on blood coagulation profile of diabetic Wistar rats. The effect of 100 mg/kg body weight of the methanol extract and partitioned fractions of C. crepidioides on blood coagulation profile of STZ-induced diabetic rats were initially evaluated, while graded concentrations (50–200 mg/kg body weight) of the aqueous and hexane fractions were further tested in diabetic rats against standard drugs aspirin (anticoagulant) and metformin (antidiabetic). Rats were allocated into groups (n = 6) and administration was done orally, once daily for 2 weeks. The methanol extract and fractions of C. crepidioides at concentrations of 50, 100, and 200 mg/kg significantly prolonged the bleeding (58–200%), clotting (65–133%), prothrombin (176–441%), and activated partial thromboplastin (209–518%) times in diabetic rats compared to the control rats (LD50 ≥ 5000 mg/kg). Highest prolongation effects were recorded in the diabetic group treated with 100 mg/kg body weight of the hexane fraction. Plasma calcium concentration and platelet counts of C. crepidioides treated diabetic rats were significantly (P<0.05) reduced compared to diabetic control rats, while the red blood cells (RBC), hemoglobin concentration, and packed cell volume (PCV) were significantly increased. This study showed that C. crepidioides possess anticoagulant and antianemic activities. The leaves can thus be a potential source of novel anticoagulant and nutraceutical for management of the thrombotic disorder in diabetes and other diseased states.